2017
DOI: 10.1038/s41598-017-17384-0
|View full text |Cite
|
Sign up to set email alerts
|

mTORC1 Signaling is a Critical Regulator of Postnatal Tendon Development

Abstract: Tendons transmit contractile forces between musculoskeletal tissues. Whereas the biomechanical properties of tendons have been studied extensively, the molecular mechanisms regulating postnatal tendon development are not well understood. Here we examine the role of mTORC1 signaling in postnatal tendon development using mouse genetic approaches. Loss of mTORC1 signaling by removal of Raptor in tendons caused severe tendon defects postnatally, including decreased tendon thickness, indicating that mTORC1 is neces… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
22
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 42 publications
2
22
0
Order By: Relevance
“…Studies in mouse have shown that activation of mTORC1 signaling in tendons causes impaired collagen fibrillogenesis, disorganized fibers, hypercellularity, and neovascularization 35 and it is possible that this is similar to what we describe in our two patients. Studies in mouse have shown that activation of mTORC1 signaling in tendons causes impaired collagen fibrillogenesis, disorganized fibers, hypercellularity, and neovascularization 35 and it is possible that this is similar to what we describe in our two patients.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…Studies in mouse have shown that activation of mTORC1 signaling in tendons causes impaired collagen fibrillogenesis, disorganized fibers, hypercellularity, and neovascularization 35 and it is possible that this is similar to what we describe in our two patients. Studies in mouse have shown that activation of mTORC1 signaling in tendons causes impaired collagen fibrillogenesis, disorganized fibers, hypercellularity, and neovascularization 35 and it is possible that this is similar to what we describe in our two patients.…”
Section: Discussionsupporting
confidence: 85%
“…In 2010, Ogino et al described35 cases with muscular hypertrophy of the hands and/or arms. Similar to our patient 1, 34 out of 35 had unilateral involvement.…”
mentioning
confidence: 99%
“…The failure to digest lysosomal glycogen to glucose may deprive muscle cells of energy source, thus initiating autophagic response to glucose starvation. Activation of AMPK-TSC pathway and inhibition of mTORC1 activity in cultured GAA-deficient myotubes and in muscle of KO mice support this hypothesis [67,68]. Alternatively, the diminished mTORC1 activity and ensuing induction of autophagy in the diseased muscle may be the initial insult originating from the inability of the damaged lysosomes to provide a proper platform for activation of this kinase.…”
Section: Lysosomes and Autophagy In Pompe Diseasementioning
confidence: 87%
“…The autophagic buildup has a profound effect on vesicular trafficking and prevents efficient delivery of the therapeutic enzyme in muscle cells [65,69]. Several attempts have been made to manipulate autophagy in muscle of KO mice by using genetic approaches: 1) genetic suppression of autophagy by inactivation of a critical autophagic gene, Atg7, in muscle of KO mice resulted in a significant reduction of lysosomal glycogen burden, thus serving as a substrate reduction therapy [70]; 2) overexpression of TFEB and TFE3 in GAA-deficient muscle cells and in muscle of KO mice stimulated autophagosomal-lysosomal fusion and exocytosis, reduced lysosomal size and glycogen content, and lessened the amount of cellular debris [65,66]; 3) activation of mTORC1 in KO mice by knocking down its inhibitor, TSC2, largely rescued autophagic defect and reversed muscle atrophy [67,68]. The common thread that runs throughout these experiments is that the currently available enzyme replacement therapy works well if skeletal muscle is cleared of autophagic buildup.…”
Section: Lysosomes and Autophagy In Pompe Diseasementioning
confidence: 99%
“…While the alterations in tendon and ligament size and cellularity may be a result of alterations in the collagen extracellular matrix, it could also be associated with alterations in cellular signaling. In this regard, transforming growth factor beta (TGF-β signaling is upregulated in bones from Crtap -/- mice 28 , and elevated TGF-β signaling has been noted in mouse models with increased tendon cellularity and alterations in collagen fibril distribution 29 . Further research is needed to elucidate the mechanisms that contribute to the histological features noted within both tendons and ligaments in these mice.…”
Section: Discussionmentioning
confidence: 99%